Development of a head-mounted eye tracker for human-computer interaction - Ong, Li Kang (2024)
This paper outlines the design, creation, and integration of an affordable head-mounted eye tracker system specifically designed for applications involving human-computer interaction (HCI). The technology employs easily accessible webcams and 3D-printed parts to create a lightweight and cost-effective eye-tracking gadget. The gaze detection software framework utilizes the Pupil Capture program, which has been developed by Pupil Labs. This ensures precise and dependable eye tracking.